Weibel-Palade bodies – secretory organelles at the interface of inflammation and hemostasis - Terglane, Julian; Gerke, Volker (Frontiers in Cell and Developmental Biology, 2025)
Weibel-Palade bodies (WPB) are lysosome-related, secretory organelles unique to vascular endothelial cells. They serve as storage organelles for the pro-thrombotic and hemostatic glycoprotein von-Willebrand factor (VWF) as well as numerous other proteins involved in regulating local inflammatory responses and coagulation processes. WPB undergo a complex formation and maturation process mainly dictated by the post-translational maturation of VWF itself. They are born at the trans-Golgi network and then move on microtubules to the cell periphery where they are anchored at the actin cortex to await signals triggering their evoked exocytosis. During this process, VWF undergoes significant compaction that results in an elongated, cigar-like shape of the organelle. WPB also receive material from the endosomal system although the trafficking routes involved here have not been fully unveiled. Exocytosis of WPB is induced by various agonists signaling through intracellular Ca2+ or cAMP elevation. It requires mobilization of WPB from the actin cortex and involves a number of docking and fusion mediating protein assemblies. The evoked release of WPB contents converts the endothelial cell surface from a repellant one which permits unrestricted blood flow to an adhesive structure capable of interacting with circulating leukocytes and platelets. Thereby, the endothelium can initiate inflammatory processes and hemostasis when vessel injury has occurred. This review discusses recent developments in the maturation and exocytosis of WPB, focusing on the ionic milieu required for tight VWF packing, endosome-to-WPB transport of WPB cargo, and WPB exocytosis and cargo release.